Innovative approach to realize the student-centered studying the discipline «Information technology in pharmacy» by foreign students - S. V. Velma (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Competence-based approach is suggested to increase the efficiency and quality of studying process. The approach is applied to «Information Technology in Pharmacy» discipline for foreign students. Textbook «Information Technology in Pharmacy» is developed by the Pharmaco-informatics department to form the professional information-technology competence of future specialists, which is based on student-centered studying. This textbook allows to provide the individual trajectory of studying for each student.